???????? ??????? ?? ????? ????? - Inawati Inawati (Jurnal Ilmiah Ilmu Ushuluddin, 2012)
The quality of a hadith can be seen through sanad or matan. It also can be found onhadith that speaks about the primacy of surah in the Qur'an for example: 1.The primacyof reading once of the surah yasin like reading Qur'an tne times, it because of Yasin is theheart of the Qur'an. 2. The virtue of surah al waqi'ah when it is read every night, wouldnot poverty stricken. 3. Surah Arrahman as the bride of the Quran. 4. Surah alBaqarah as the highest of the Qur'an. After it was researched and examined by thehadith scholars, it is going controversies among the narrators of hadith, so it weakening ofthe hadith. The problem is the law to practice with the weak hadith. Some scholars arguethat it can be used as proof, but with strict conditions sufficient conditions, namely: 1. Theweakness of hadith is not too severe. 2. There is another argument that is essential for aweak hadith. 3. Practice is not intended as instructions from these traditions, but on thebasis of intended ikhtiyath (prudent)